Juegos autóctonos y populares del pueblo montubio como elemento para fortalecer al cantón Balzar de la Provincia del Guayas - Diaz Loor, Flor Nathaly (2020)
This research is aimed at rescuing the native and popular games of the Montubio people as an element to strengthen the Balzar canton of the province of Guayas, activities currently forgotten that can help in the aggrandizement of the city by activating tourism and in turn reviving the economy local that is based solely on agriculture mainly of corn and rice. It is very important to emphasize that when the local tourism is reactivated, the quality of life of its population will be significantly improved because a new source of work will be created, the number of visitors will increase and the canton will begin to take competitive advantages that will generate more profitability in the Commerce. In the stage of data collection through the survey, it was possible to rescue that a large percentage of citizens wish to rescue the native montubios games that used to enhance it in the festivities as well as in the school. In the approach of the problem it was detailed that Canton Balzar adjoins many nearby cantons such as Palestine, Empalme and Daule, Palestine and Guayaquil, a strategic place to carry out commercial, cultural and tourist activity that justifies the idea of rescuing traditional montubios games. As recommendations, the alternative of coordinating with government, educational and security authorities was proposed to have the support of encouraging tourism in the canton of Balzar by reviving traditional games